Gestión administrativa de la Microempresa Pc Móvil Soluciones de la Parroquia San Juan, Cantón Puebloviejo. - Vásquez Villamar, Nayelin Narcisa (2022)
This case study focuses on the administrative management of the microenterprise PC Móvil Soluciones S.A. company operating since 2017; within which shortcomings were detected such as: it does not have an established organizational structure, nor is it carried out an adequate direction of its activities to improve its productivity, among others, for which the main objective is to analyze the incidence of administrative management with the decision-making of the Microenterprise PC Móvil Soluciones, in order to provide an adequate process and thus guarantee a quality service. To carry out the research, descriptive and inductive methods are used to better understand the problematic situation, just as the survey and interview were used as collection techniques that allow obtaining the results. Through these techniques it was possible to know that the majority of employees claim to have knowledge of administrative strategies, that there is no established administrative process; Likewise, the lack of knowledge about administrative management by the manager was revealed, which has had consequences both in decision-making and in customer satisfaction.